Iron and ferritin accumulate in separate cellular locations in Phaseolus seeds - Cvitanich, C; Przybylowicz, WJ; Urbanski, DF; Jurkiewicz, AM; Mesjasz-Przybylowicz, J; Blair, Matthew W.; Astudillo, Carolina; Jensen, E; Stougaard, J (Springer, 2010)
Background: Iron is an important micronutrient for all living organisms. Almost 25% of the world population is affected by iron deficiency, a leading cause of anemia. In plants, iron deficiency leads to chlorosis and reduced yield. Both animals and plants may suffer from iron deficiency when their diet or environment lacks bioavailable iron. A sustainable way to reduce iron malnutrition in humans is to develop staple crops with increased content of bioavailable iron. Knowledge of where and how iron accumulates in seeds of crop plants will increase the understanding of plant iron metabolism and will assist in the production of staples with increased bioavailable iron.